2013
DOI: 10.1089/jpm.2012.0243
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Financial Impact of an Inpatient Acute Palliative Care Unit in a Tertiary Care Teaching Hospital

Abstract: Cost avoidance is realized when patients transfer to an APCU even when conservative pre-APCU cost measures are used and when patients with varying diagnoses and discharge outcomes are included. This study demonstrates a replicable methodology for estimating the financial impact of an APCU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…Early timing of PCM involvement in ICU is associated with both lower ICU mortality rate and LOS. Furthermore, dedicated inpatient PCM units capable of providing care to patients requiring mechanical ventilation and/or vasoactive therapy would result in a better delivery of end‐of‐life care, as terminal critically ill patients can be transitioned out of the ICU to these units for such purposes . Although our institution has a PCM service available at all times, just 18 patients (25.4%) in the present study had advance directives during their hospitalization: 15 (83.3%) were obtained in ICU, and the rest in the ED.…”
Section: Discussionmentioning
confidence: 90%
“…Early timing of PCM involvement in ICU is associated with both lower ICU mortality rate and LOS. Furthermore, dedicated inpatient PCM units capable of providing care to patients requiring mechanical ventilation and/or vasoactive therapy would result in a better delivery of end‐of‐life care, as terminal critically ill patients can be transitioned out of the ICU to these units for such purposes . Although our institution has a PCM service available at all times, just 18 patients (25.4%) in the present study had advance directives during their hospitalization: 15 (83.3%) were obtained in ICU, and the rest in the ED.…”
Section: Discussionmentioning
confidence: 90%
“…Given that cost of care upon admission to a hospital is generally higher than at other times as a result of diagnostics, Pre-PCU costs were determined by the mean daily costs of two days before transfer for each patient encounter, which is an established method. 20 To assess the PCU costs, we calculated the mean daily variable costs of the entire PCU length of stay. The mean daily variable costs of Pre-PCU and PCU were multiplied by the number of patients transferred to the PCU (153) and by the average length of stay in the PCU (5.11 days) to generate total variable costs per group.…”
Section: Pcu Cost Minimizationmentioning
confidence: 99%
“…Daily variable costs of PCU are on the basis of the overall costs outlined in Table 1; however, daily variable costs of Pre-PCU use are determined by the mean daily costs for 2 days before transfer. 20 We multiplied the daily costs per patient encounter by the number of patients (153) and average length of stay (5.11 days). The cost savings are the difference between these products.…”
Section: Pcu Cost Minimizationmentioning
confidence: 99%
“…T here is a growing evidence base supporting the observation that inpatient palliative care (IPC) consultation services reduce length of stay (LOS) and hospital costs [1][2][3][4][5][6][7] while concurrently increasing patient and provider satisfaction, 8,9 improving symptom control, 10 and increasing advance directive completion. 11,12 In addition, studies have shown that IPC services reduce the likelihood of intensive care unit (ICU) readmission.…”
Section: Introductionmentioning
confidence: 99%